GE_GERICHTE C/991/2017 vom 7. Mai 2018 - GE Cour de justice (2018)
BAIL À LOYER ; CONTESTATION DU CONGÉ ; MOTIF ; PROLONGATION DU BAIL À LOYER ; PESÉE DES INTÉRÊTS | CO.266; CO.271; CO.271.leta; CO.272